Relationship between differentiation of self and attitude towards physician-nurse relationship in hospitals (Isfahan/Iran) - SeyedMeysam Jafary; Mousa Alavi; Alireza Irajpour; Tayebeh Mehrabi (Wolters Kluwer Medknow Publications, 2017)
Background: Attitude towards physician-nurse relationship is fundamental to achieve health care quality. Such attitude maybe determined by some personality traits such as differentiation of self. Hence, the present study aimed to investigate the relationship between differentiation of self and attitude to professional physician-nurse relationship. Materials and Methods: This cross-sectional study was done in three hospitals in Isfahan in 2015. The study included all nurses and physicians. In total, 400 participants were recruited through convenience-sampling method. Data gathering instruments included a three-part questionnaire [demographic data sheet, Jefferson Scale of Attitudes toward Physician-Nurse Collaboration (JSAPNC) and differentiation of self-inventory (DSI)]. The data were analyzed through descriptive and inferential statistics [t-test, analysis of variance (ANOVA), and multiple linear regression) by the Statistical Package for the Social Sciences (SPSS) version 16 software. Results: The mean [standard deviation (SD)] of the scores of differentiation of self in physicians and nurses were 86.43 (9.62) and 159.28 (9.53), respectively. The results showed that the predicting model of attitudes towards physician-nurse relationship based on dimensions of differentiation of self both in nurses and physicians were significant. Moreover, the findings from linear regression analyses showed that predictor variables explained 0.18 and 0.14 of the variance of attitudes towards physician-nurse relationships in nurses and physicians, respectively. Conclusions: Considering the significant role of differentiation of self to predict attitudes towards physician-nurse relationship, it is worthwhile to suggest provision of training programs particularly in the nursing and medical students to enhance differentiation of self both in physicians and nurses to improve culture of interprofessional relationships and to achieve optimum professional relationships between doctors and nurses.